Salt-responsive bermudagrass microRNAs and insights into light reaction photosynthetic performance - Fan, Shugao; Amombo, Erick; Avoga, Sheila; Li, Yating; Yin, Yanling (Frontiers in Plant Science, 2023)
Introduction Bermudagrass (Cynodon dactylon L.) is a warm-season grass with high drought and salt tolerance. However, its cultivation as a silage crop is limited by its lower forage value when compared to other C4 crops. Because of its high genetic variability in abiotic stress tolerance, bermudagrass-mediated genetic breeding offers significant promise for introducing alternative fodder crops in saline and drought-affected regions, and improved photosynthetic capacity is one way for increasing forage yield. Methods Here, we used RNA sequencing to profile miRNAs in two bermudagrass genotypes with contrasting salt tolerance growing under saline conditions. Results Putatively, 536 miRNA variants were salt-inducible, with the majority being downregulated in salt-tolerant vs sensitive varieties. Also, seven miRNAs putatively targeted 6 genes which were significantly annotated to light reaction photosynthesis. Among the microRNAs, highly abundant miRNA171f in the salt tolerant regime targeted Pentatricopeptide repeat-containing protein and dehydrogenase family 3 member F1 both annotated to electron transport and Light harvesting protein complex 1 genes annotated to light photosynthetic reaction in salt tolerant regime vs salt sensitive counterparts. To facilitate genetic breeding for photosynthetic capacity, we overexpressed miR171f in Medicago tracantula which resulted in a substantial increase in the chlorophyll transient curve, electron transport rate, quantum yield of photosystem II non photochemical quenching, NADPH and biomass accumulation under saline conditions while its targets were downregulated. At ambient light level the electron transport was negatively correlated with all parameters while the NADPH was positively associated higher dry matter in mutants. Discussion These results demonstrate that miR171f improves photosynthetic performance and dry matter accumulation via transcriptional repression of genes in the electron transport pathway under saline conditions and thus a target for breeding.